Mineral elements in muscat sage plant (Salvia sclarea L.) and essential oil - Szentmihályi, Klára (Acta Biologica Szegediensis, 2009)
The authors investigated the element content of different parts of muscat sage plant (Salvia sclarea L.) by ICP-OES for 18 elements (Al, B, Ca, Cr, Cu, Fe, K, Li, Mg, Mn, Mo, Na, Ni, P, Pb, S, V, Zn) and the composition of muscat sage oil during distillation by GC-MS. The essential oil was obtained by steam distillation. High Li and Cr concentration was found in plant samples. The essential oil was characterized by four main components: linalool, carvon, linalyl acetate and geranyl acetate and the composition of oil was unchanged during distillation.